1991
DOI: 10.1111/j.1745-3992.1991.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Intrajudge Consistency During Standard‐Setting

Abstract: What factors influence judges when they set standards? How do judges, test questions, and the standard‐setting process interact? How can we improve intrajudge consistency?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…Potential causal factors of inconsistencies both within and between judges have been classified into three categories: (a) the background of judges, (b) the items and their contexts, and (c) the standard-setting processes (Plake et al, 1991). Concerning the judge-related factors Chang et al (1996) showed that when judges differ in their conceptualisation of minimal competency, judgemental inconsistencies may arise.…”
Section: Introductionmentioning
confidence: 99%
“…Potential causal factors of inconsistencies both within and between judges have been classified into three categories: (a) the background of judges, (b) the items and their contexts, and (c) the standard-setting processes (Plake et al, 1991). Concerning the judge-related factors Chang et al (1996) showed that when judges differ in their conceptualisation of minimal competency, judgemental inconsistencies may arise.…”
Section: Introductionmentioning
confidence: 99%
“…A computerized procedure will also permit constant monitoring of the consistency of the judges' performance Downloaded by [University of Washington Libraries] at 18:28 04 April 2015 during training and facilitate intrajudge consistency during the standard-setting process (Plake et al, 1991). The judges' confidence in their decisions can also be assessed and correlated with their consistency.…”
Section: Preliminary Stepsmentioning
confidence: 99%
“…The research on factors that influence judges' ratings during training and the stages of standard setting deal almost exclusively with item judgments and defining minimal competence (Melican & Mills, 1986& Mills, , 1987Mills, Melican, & Ahluwalia, 1991;Norcini, Shea, & Kanya, 1988;Plake, Melican, & Mills, 1991;Pulakos et al, 1989;Smith & Smith, 1988). Despite the limited focus of these studies, the criteria proposed by Reid (1991) for evaluating training effectiveness based on their findings can be generalized to the more recent standard-setting methods: (a) Judgments should be stable over time, (b) judgments should be consistent with item and test score performance, and (c) judgments should reflect realistic expectations.…”
Section: Preliminary Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, iterations aimed at inter-judge consistency are open to "social influence effects by dominant committee members" [37] and "the dynamics of the group discussion", including the desire to appear professional. [7] Consequently, convergence of scores can reflect submission to peer pressure rather than identification of a valid standard.…”
Section: Post-hoc Revisions and The Threat To Validitymentioning
confidence: 99%